Penerapan Motivasi Dalam Proses Pebelajaran - Nidawati (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Motivation is one of the factors that influences student success in the learning process. Students will get the desired results in learning if within them there is a desire to learn. Motivation can function as a driving force for achieving good results. Students will carry out an activity because there is motivation within them. Having high motivation in learning will achieve optimal results. To achieve optimal results, teachers must give maximum effort and attention to students, especially for students whose achievements are lagging behind other students, so that these students are more motivated in participating in teaching and learning process activities so that what they want can be achieved optimally so that achieve the desired goals, both in the field of education and other goals. By having high motivation, students can develop activities and initiative, can direct and maintain persistence in carrying out learning activities to achieve the desired educational goals.